The Effects of County Public Hospital Reform on the Consumption and Costs of Antibiotics: Evidence from a Quasinatural Experiment in Jiangsu, China. (22nd October 2020) - Wang, Ying; Zhu, Yulei; Liu, Xiaoliang; Xu, Xinglu; Fang, Wenqing; Li, Xin
Abstract : Background . Overuse of antibiotics is a major driver for rapid spread of antimicrobial resistance worldwide, particularly common in China. The close linkage between hospital revenue and sales of drugs has become the key incentive for overprescription of antibiotics. Since 2009, the Chinese government implemented a series of measures to cut off the link, including removing the markup of drugs, increasing financial subsidies, and adjusting charges for medical service. Objective . To evaluate the impacts of county public hospital reform on the consumption and costs of procured antibiotics in Jiangsu province. Methods . A quasiexperiment design was conducted in Jiangsu province where 99 county public hospitals implemented the reform successively in different periods. Of these, 37 county public hospitals implemented the reform since January 2013, which were regarded as the intervention group, and the remaining 62 hospitals were included in the control group. A difference-in-differences (DID) analysis with generalized linear regressions was used on the procurement records of antibiotics from January 2012 to December 2013. Modified Park test was used for family distribution and Box–Cox test for log link. Placebo tests were employed to test the common-trend hypothesis of two groups. Results . For the intervention group, the average volume of procured restricted antibiotics and injectable antibiotics increased by 24.12% and 2.75% while the costs increased by 19.01% and 9.09%, respectively. The average costs per DDD of restricted and injectable antibiotics were much higher than unrestricted and oral antibiotics. The DID results showed that the reform had a positive impact on the average volume (p = 0.005 ) and costs (p = 0.001 ) of nonrestricted antibiotics. In addition, the implementation of the reform was associated with a reduction in volume (p = 0.031 ) and costs (p = 0.043 ) of procured oral antibiotics. The reform also contributed to an increase in average costs per DDD of total antibiotics (p = 0.049 ). Conclusions . The reform is effective in reducing the consumption and costs of unrestricted and oral antibiotics, but it has failed to reduce the consumption and costs of expensive restricted and injectable antibiotics, leading to increased burden of diseases. It is critical that the health policy initiatives can deincentivize overuse of antibiotics at both hospital and individual physician's levels. The reform should enforce government financial support, improve hospital governance, optimize performance evaluation, and establish specialized management approach for antibiotic use.